Generation of suppressor macrophages during the human autologous mixed lymphocyte reaction. - Pretell, J O (1986)
The suppression of a mixed lymphocyte culture (MLC) by cells generated in an autologous mixed lymphocyte reaction (AMLR) is an in vitro assay which has been used to monitor immune regulation by T cells in patients with suspected autoimmune disorders. We found that the cells generated in an AMLR which were predominantly responsible for the suppression of an MLC were not T cells, but rather large, low density cells bearing macrophage cell surface determinants (M1 & M5). Generation of these cells appeared not to require either E-rosette positive T cells, or cell division, as gamma-irradiated E-rosette negative cells cultured alone for 6 days gave rise to these cells as well. Enrichment for the large AMLR-generated cells by discontinuous density gradient separation yielded a population of cells which were highly suppressive compared to the smaller cells, the majority of which bore T cell surface markers and which had little effect or even enhanced an MLC. Peripheral blood mononuclear cells cultured under similar conditions, but without prior separation and irradiation of the E-rosette negative cells also were shown to generate a population of large suppressor cells bearing M1 and M5 determinants. These findings suggest that these large macrophage-like suppressor cells are not an artifact of cell separation by rosetting with sheep erythrocytes and that such cells as well as T cells may be critical in the regulation of immune responses in vivo as well as in vitro.